2010
DOI: 10.1073/pnas.0908101107
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry imaging of mating Tetrahymena show that changes in cell morphology regulate lipid domain formation

Abstract: Mass spectrometry imaging has been used here to suggest that changes in membrane structure drive lipid domain formation in mating single-cell organisms. Chemical studies of lipid bilayers in both living and model systems have revealed that chemical composition is coupled to localized membrane structure. However, it is not clear if the lipids that compose the membrane actively modify membrane structure or if structural changes cause heterogeneity in the surface chemistry of the lipid bilayer. We report that tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
80
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 37 publications
0
80
0
1
Order By: Relevance
“…Dipalmitoylphosphatidylcholine (DPPC) is one of the phospholipid molecules that has been extensively studied using ToF-SIMS [38][39][40]. The most characteristic peak of DPPC is the m/z 184 signal, [C 5 H 15 NO 4 P] + , which represents the head group of a DPPC molecule.…”
Section: Signal Improvement Of Biofilm and Cell Samplesmentioning
confidence: 99%
“…Dipalmitoylphosphatidylcholine (DPPC) is one of the phospholipid molecules that has been extensively studied using ToF-SIMS [38][39][40]. The most characteristic peak of DPPC is the m/z 184 signal, [C 5 H 15 NO 4 P] + , which represents the head group of a DPPC molecule.…”
Section: Signal Improvement Of Biofilm and Cell Samplesmentioning
confidence: 99%
“…Previous studies have focused on changes in lipid composition during cellular events such as mating [27] and cell division. [28] Ostrowski et al showed that the conjugation site of two mating Tetrahymena had an increased 2-aminoethylphosphonolipid (2-AEP)/phosphatidylcholine (PC) ratio indicating an increase in conical shaped lipids that are associated with high membrane curvature.…”
Section: Tetrahymenamentioning
confidence: 98%
“…Previous studies demonstrated replacement of cylindrical lipid species at the exchange junction with nonlamellar species that can support tight curvature during conjugation (37,38). The margins of exchange junction pores and, later, the tubular curtain they transform into represent expanding regions of tight membrane curvature.…”
Section: Conjugation In the Ciliatementioning
confidence: 99%